2014
DOI: 10.1186/1471-2164-15-520
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of ZNF217 chromatin occupancy in the breast cancer cell genome reveals an association with ERalpha

Abstract: BackgroundThe ZNF217 gene, encoding a C2H2 zinc finger protein, is located at 20q13 and found amplified and overexpressed in greater than 20% of breast tumors. Current studies indicate ZNF217 drives tumorigenesis, yet the regulatory mechanisms of ZNF217 are largely unknown. Because ZNF217 associates with chromatin modifying enzymes, we postulate that ZNF217 functions to regulate specific gene signaling networks. Here, we present a large-scale functional genomic analysis of ZNF217, which provides insights into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…Additionally, we have shown that the estrogen-induced miRNA, miR-503, targets the 3 ′ -UTR of ZNF217 and that while miR-503 is induced in response to estrogen, the oncogene ZNF217 is reduced. In support of this relationship, data from breast cancer patient cohorts show that high expression of ZNF217 is associated with worse survival (Gyorffy et al 2009;Frietze et al 2014), while high expression of miR-503 is associated with improved survival (Antonov 2011;Lyng et al 2012;Antonov et al 2013). Furthermore, while this manuscript was under review, another study was published demonstrating that the GATA3-driven expression of miR-503 represses ZNF217 in prostate cancer (Jiang et al 2016).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Additionally, we have shown that the estrogen-induced miRNA, miR-503, targets the 3 ′ -UTR of ZNF217 and that while miR-503 is induced in response to estrogen, the oncogene ZNF217 is reduced. In support of this relationship, data from breast cancer patient cohorts show that high expression of ZNF217 is associated with worse survival (Gyorffy et al 2009;Frietze et al 2014), while high expression of miR-503 is associated with improved survival (Antonov 2011;Lyng et al 2012;Antonov et al 2013). Furthermore, while this manuscript was under review, another study was published demonstrating that the GATA3-driven expression of miR-503 represses ZNF217 in prostate cancer (Jiang et al 2016).…”
Section: Discussionmentioning
confidence: 78%
“…2C)-all critical genes to the etiology of breast cancer (Sørlie et al 2001;Usary et al 2004;Oh et al 2006;Cohen et al 2015). ZNF217, a no- (Cohen et al 2015) and has been identified as a biomarker of poor survival in patients with Luminal A (ER+) breast tumors (Frietze et al 2014). Approximately 40% of the genes in the repressed class were previously identified as down-regulated at 24 h after estrogen stimulation (Jagannathan and Robinson-Rechavi 2011).…”
Section: Dynamics Of Estrogen-regulated Mrnasmentioning
confidence: 99%
See 3 more Smart Citations